Warung Segar's Digital Branding Strategy in Growing Interest in Online Groceries Shopping - Olga Tiara; Feliza Zubair; Yustikasari Yustikasari (Ikatan Sarjana Komunikasi Indonesia, 2023)
The COVID-19 pandemic has a significant impact on the survival of startup business units. Startups are required to design brilliant strategies to survive. One of the strategies that startups can do is the digital branding process, which allows startups to have a strong position in the market. This study of Warung Segar's branding strategy in Growing Interest in Groceries Shopping Online uses qualitative methods and a case study approach. Qualitative research looks at the ideas, observations, opinions, and beliefs of the people studied. The purpose of the study is to find out how the technology, elements, processes and operations of Startup Warung Segar do digital branding in order to grow the interest of Groceries Shopping Online. The results of the study provide results that Warung Segar which has used Digital Branding can survive and is able to boost sales with a market oriented branding approach, Warung Segar has an understanding of the urgency of internal branding as a manifestation of the Spirit of Goodness which is based on integration and comprehensive treatment of the brand.